2009
DOI: 10.1001/archoto.2009.71
|View full text |Cite
|
Sign up to set email alerts
|

Speech Intelligibility, Acceptability, and Communication-Related Quality of Life in Chinese Alaryngeal Speakers

Abstract: In speech rehabilitation after laryngectomy, QOL and speech intelligibility and acceptability should be considered together to find a balance that is acceptable to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 20 publications
2
43
0
4
Order By: Relevance
“…Measures of “communication effectiveness” have been used to assess a variety of everyday situations for individuals with ALS (Ball, Beukelman, & Pattee, 2004) and PD (Donovan, Kendall, Young, & Rosenbek, 2008). Examples of other questionnaires that touch on communicative participation, among other topics include the Dysarthria Impact Profile (Walshe, Peach, & Miller, 2009) and Living with Neurologically Based Speech Difficulties (LwD) (Hartelius, Elmberg, Holm, Lovberg, & Nikolaidis, 2008) for dysarthria; The Communication Activity and Participation After Laryngectomy questionnaire (I. Law, Ma, & Yiu, 2009) for laryngectomy, and the Overall Assessment of the Speaker’s Experience of Stuttering (OASES) for stuttering (Yaruss & Quesal, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Measures of “communication effectiveness” have been used to assess a variety of everyday situations for individuals with ALS (Ball, Beukelman, & Pattee, 2004) and PD (Donovan, Kendall, Young, & Rosenbek, 2008). Examples of other questionnaires that touch on communicative participation, among other topics include the Dysarthria Impact Profile (Walshe, Peach, & Miller, 2009) and Living with Neurologically Based Speech Difficulties (LwD) (Hartelius, Elmberg, Holm, Lovberg, & Nikolaidis, 2008) for dysarthria; The Communication Activity and Participation After Laryngectomy questionnaire (I. Law, Ma, & Yiu, 2009) for laryngectomy, and the Overall Assessment of the Speaker’s Experience of Stuttering (OASES) for stuttering (Yaruss & Quesal, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, past research findings have suggested uncertainty relative to potential relationships between listener‐rated and patient‐reported outcomes; this uncertainty has persisted because very few studies have investigated both types of outcomes in the same group of speakers. Yet, even among the few studies that have been conducted, results have only revealed weak relationships between these measures . Meyer et al did not find any significant relationships between clinician‐rated speech intelligibility and patient‐reported outcomes in 16 individuals who had undergone total laryngectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are clear acoustic and listener‐rated differences among alaryngeal methods, there is some controversy about whether patient‐reported outcomes show similar results . Inconsistencies are revealed when different types of outcome measures are used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Further, studies investigating intelligibility and acceptability characteristics between TE and ES speakers have also reported TE speakers' speech to be more intelligible and acceptable compared to ES speakers. [8][9][10][11][12][13][14] Most of the above mentioned studies which have compared TE and ES modes of alaryngeal speech have used different speakers for each speaking mode, and generally report large inter-participant variability among the participants within each mode. Although such an approach is useful in investigating the obvious differences between TE and ES modes, the differences noticed in those studies, between two alaryngeal modes, can also be influenced by other factors such as differences in the anatomy of voice source (placement of PE segment), differences in the length of the vocal tract, articulation ability, and speaking proficiency.…”
Section: Introductionmentioning
confidence: 99%